Nexus of financial development and economic growth in the Asian region countries with technological advancements as the moderator / Hewage Rishan Sampath - Sampath, Hewage Rishan (2023)
Since the early nineteenth century, scholars have paid attention to verifying Financial Development (FD) and Economic Growth nexus (EG) but the results are vague concerning causality and linearity among FD and EG. Further from the late nineteenth, scholars added Technological Advancement (TA) to the list since TA makes miracles to boost economies. However, they understood that the influence of FD and TA towards EG is affected by structural breaks. Hence, intellectuals have attempted to examine the effect of structural breaks on economic activities to assess the relationship of FD, TA and EG. Thus, this study ran on four objectives, first, to examine FD and EG nexus in Asian regional countries, second to identify the effect of FD to EG concerning income level difference of individual countries. The third is to assess the moderator effect of TA towards FD and EG nexus and the final is to assess the effect of structural breaks to FD and EG nexus. The sample consisted of 34 Asian countries and data were gathered for 20 years from 2000 to 2019. FD and TA were the explanatory variables while EG was the response variable. In addition to key independent variables, Human Capital (HC) and Private Consumption (PC) were taken as control variables. The Global Economic Crisis was considered to examine the effect of structural break outbreaks. The study followed short-panel and long-panel data analysis techniques and the results indicated that all the independent variables significantly affect to EG. Further, FD and PC have a significant negative effect on EG whereas TA and HC have a positive connection with EG. However, these relationships vary with income level disparities of individual countries. In addition, the results showed that the moderator effect of TA is negative indicating that despite there being a positive effect of TA to EG as individual variables, the interaction effect of TA while blending with FD shows negative results. Last but not least the third objective of the study was to examine the effect of structural break where the analysis confirms that there is a significant effect of Global Financial Crisis to change the relationships of FD, TA, HC and PC with EG. Hence, the outcomes of this study contribute to guiding the policymakers in developing sustainable policies in terms of Asian region and individual countries and to maintaining better investment portfolios to maintain appropriate levels of FD, TA, HC and PC while vigilant on structural breaks.